Uniaxial Compression Mechanical Analysis of Cylindrical Rock Specimens Based on Space Axisymmetric Problem - Jianguang Li; Yanchun Wang; Chuanqi Su (Shock and Vibration)
The common failure forms in the uniaxial compression test of standard cylindrical rock specimens are symmetric cone failure and splitting failure. In the past, two kinds of failure forms were explained from the plane problems of elasticity theory. However, there was a lack of research based on space problems. In this paper, based on spatial axisymmetric elastic mechanics theory, three-dimensional stress function is constructed for the cylindrical rock specimen under uniform axial compression by adopting the semi-inverse method. According to the stress function, the stress components and the principal stress are deduced when considering the end effect. The failure form is speculated, which can well explain the two common types of damage in uniaxial compression. This work may enrich the basic research of rock mechanics.